Workplace Conditions and Organizational Commitment in Shaping Turnover Intention among Generation Z Employees - Agus Suyatno; Rokhimah Rokhimah (Goodwood Publishing, 2026)
Purpose: This study examines the determinants of turnover intention among Generation Z employees in Indonesia and investigates the moderating role of organizational commitment in the relationship between job satisfaction and turnover intention Research Methodology: A quantitative survey was conducted using an online questionnaire distributed to 258 Generation Z employees with 6–12 months of work experience across various sectors in Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0, employing validated measurement scales from prior studies. Results: The results indicate that work environment (β = –0.278, p = 0.000), work–life balance (β = –0.036, p = 0.049), job satisfaction (β = –0.421, p = 0.000), and organizational commitment (β = –0.129, p = 0.028) significantly reduce turnover intention. Conversely, workload (β = 0.024, p = 0.687) and salary satisfaction (β = 0.101, p = 0.265) show no significant effects. The moderating effect of organizational commitment on the relationship between job satisfaction and turnover intention is not significant (β = –0.011, p = 0.654). Conclusions: Turnover intention among Generation Z is primarily influenced by work environment, work–life balance, job satisfaction, and organizational commitment Limitations: The study is limited to early-career employees in Indonesia using cross-sectional data. Contributions: It contributes to HRM literature by clarifying key retention factors and testing the moderating role of organizational commitment in a generational context.